The Middle Stone Age human fossil record from Klasies River Main Site. Issue 103 (February 2017) - Grine, Frederick E.; Wurz, Sarah; Marean, Curtis W.
Abstract: The paleoanthropological significance of Klasies River Main Site derives from its abundant Middle Stone Age (MSA) archaeological debris and the hominin fossils that have featured in discussions about modern human emergence. Despite their significance, the human remains have yet to be contextualized within the spatial, stratigraphic and geochronological framework of the site. We provide an updated overview of the stratigraphy and geochronology of the site, and review the human fossil record in this context. We also provide the first anatomical interpretations of many of the cranial vault fragments. Five hominin specimens derive from the Upper Member and six from the lowermost LBS Member. The vast majority – nearly 40 cataloged specimens – come from the SAS Member; many of these are from a single stratigraphic horizon in a relatively small area in Cave 1. There is a strong cranial bias to the sample; just over 70% of skeletal remains are from the skull. The postcranial skeleton is poorly represented. Excluding the three metatarsals, there are only three long bones in the sample – a clavicle, a proximal radius, and a proximal ulna. Remarkably, humeral, femoral and tibial diaphyses, which are the most durable elements in terms of cortical bone thickness and density, are absent. However, the proportional representation of hominin remains is reminiscent of the "Klasies Pattern" shown by the MSA large bovid skeletal parts. To some degree, this may reflect the excavation and recovery methods that were employed. The vast bulk of the human fossils represent adults. Only three undoubted juvenile individuals are represented – each by a deciduous tooth. This contrasts with other MSA sites along the southern coast of South Africa, where human remains are predominantly juvenile, usually in the form of (possibly exfoliated) deciduous teeth. However, this apparent dissimilarity may also reflect different excavation techniques.